Growth, structural and vibrational properties of hydrogenated nanocrystalline silicon thin films prepared by radiofrequency magnetron sputtering technique at room temperature - Sonmez, Ayse; Sezgin, Nagihan; Tuna, Ocal; Ozturk, Sibel Tokdemir; Ozturk, Osman; Karabulut, Mevlut; Seyidov, MirHasan Yu (Elsevier Science Sa, 2023)
The main objective of this paper is to produce the hydrogen-free and hydrogenated nanocrystalline silicon (nc-Si: H(x)) thin films deposited onto the single-crystalline Si(100) wafer by radio-frequency magnetron sputtering (RF-MS) at a substrate temperature of -300 K. Sputtering was effectuated by a microwave plasma in a mixture of argon and hydrogen (Ar + (H2(x)) gasses taken at different proportions of hydrogen dilution: x = 0, 2.5, and 5 sccm (standard cubic centimeter per minute). The deposition rates of the nc-Si : H were fully controlled, and the thickness of these films was -200 and 300 angstrom. Pt -capping layer was deposited in order to protect the nc-Si : H layer from oxidation. The thickness of the capping layer was fixed at -5 angstrom. The effects of the hydrogen flow rate and post-growth thermal treatment on the crystalline structure and morphology of as-grown nanocrystalline silicon thin films were systematically investigated by ultraviolet and x-ray photoelectron spectroscopy (UPS and XPS), atomic force microscopy (AFM), grazing incidence x-ray diffraction (GI-XRD) and micro-Raman spectroscopy methods. From the measured data, the average nano -crystallite sizes, surface morphology and other important characteristics of these thin films were analyzed. The grown nc-Si : H thin films may be used as a semiconducting electrode material for electrochemical proton pro-duction, which is of great technological importance, especially for solid-state electrochromic device applications.
Keywords: Hydrogenated nanocrystalline silicon; Radio -frequency magnetron sputtering; Ultraviolet photoelectron spectroscopy; X-ray photoelectron spectroscopy; Atomic force microscopy; Grazing incidence x-ray diffraction; Miicro-Raman spectroscopy